Love in Catalina Cove - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Catalina Cove., 2018)
"In her brand-new series, Brenda Jackson welcomes you to Catalina Cove, where even the biggest heartbreaks can be healed. In the wake of a devastating teen pregnancy that left her childless and heartbroken, Vashti Alcindor left Catalina Cove, Louisiana, with no plans to return. Now, over a decade later, Vashti reluctantly finds herself back in her hometown after inheriting her aunt's B and B. Her homecoming gets off to a rocky start when the new sheriff, Sawyer Grisham, pulls her over for speeding, and things go downhill from there. The B and B, a place she'd always found refuge in when it seemed like the whole world was against her, has fallen into disrepair. When a surprising benefactor encourages Vashti to reopen the B and B, Vashti embraces a fresh start, and soon old hurts begin to fade as she makes new memories with the town and its handsome sheriff. But some pasts are too big to escape, and when a bombshell of a secret changes everything she thought was true, Vashti is left reeling. With Sawyer and his teenage daughter determined to see her through the storm, though, she's learning family isn't always a matter of blood- sometimes it's a matter of heart." -- Amazon.